2020
DOI: 10.1038/s41598-020-64102-4
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation of α1D-adrenergic receptor N-terminal domain is required for correct trafficking, function, and biogenesis

Abstract: G protein-coupled receptor (GPCR) biogenesis, trafficking, and function are regulated by posttranslational modifications, including N-glycosylation of asparagine residues. α 1D-adrenergic receptors (α 1D-ARs)-key regulators of central and autonomic nervous system function-contain two putative N-glycosylation sites within the large N-terminal domain at N65 and N82. However, determining the glycosylation state of this receptor has proven challenging. Towards understanding the role of these putative glycosylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…We and others have utilized SNAP-tag technology to monitor GPCR protein expression and localization in vitro. 1625 Here, we investigated the utility of incorporating SNAP-tag technology into traditional CHX-chase assays to permit calculation of GPCR protein half-lives when expressed in cultured human cells. Our experimental workflow involved fusing the SNAP-tag to the N-terminal domain of select GPCRs, transiently transfecting SNAP-GPCR cDNA constructs into HEK293 cells, and then treating cells with 50 µg/mL CHX for 0–24 h. Cells were then lysed and treated with the irreversible SNAP substrate BG-782, subjected to PAGE, and analyzed with LICOR Odyssey NIR quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have utilized SNAP-tag technology to monitor GPCR protein expression and localization in vitro. 1625 Here, we investigated the utility of incorporating SNAP-tag technology into traditional CHX-chase assays to permit calculation of GPCR protein half-lives when expressed in cultured human cells. Our experimental workflow involved fusing the SNAP-tag to the N-terminal domain of select GPCRs, transiently transfecting SNAP-GPCR cDNA constructs into HEK293 cells, and then treating cells with 50 µg/mL CHX for 0–24 h. Cells were then lysed and treated with the irreversible SNAP substrate BG-782, subjected to PAGE, and analyzed with LICOR Odyssey NIR quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the primary goal of this study was to develop a simple, reproducible approach that can be used to quantify degradation half-lives of GPCRs (and possibly other membrane proteins) in high throughput relative to traditional immunoprecipitation/immunoblotting. Previous studies in which the SNAP-tag was leveraged to identify and characterize the α 1D -AR:Scribble:dystrophin-associated protein complex, 34 determined the importance of type I PDZ ligands for GPCR functional expression, 15 or facilitated the serendipitous discovery that the α 1D -AR N-terminal domain is endogenously cleaved 19 guided the decision to incorporate the SNAP-tag into CHX-chase assays. Herein, we demonstrated that the SNAP-epitope tag is remarkably stable and does not induce degradation of β-actin, and thus is not likely enhancing GPCR degradation rates.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent report indicates that a mutant purinergic P2Y 2 receptor deficient in glycosylation undergoes ER-associated proteasomal degradation pathway, possibly due to retention in ER lipid rafts and failure of traffic to the Golgi (Nakagawa et al, 2017). A similar observation was made for a 1D -adrenoreceptor, where a glycosylation-deficient mutant displays impaired plasma membrane expression likely because of degradation via ERAD (Janezic et al, 2020). Collectively, substantial evidence suggests that N-glycosylation of GPCRs during maturation in the biosynthetic pathway is essential to achieve optimal cell surface expression.…”
Section: Expanding Gpcr Biology By Ptmsmentioning
confidence: 65%
“…Future studies using additional mutations on both the essential asparagine residue and on other proximal non-essential residues could reveal the impact of the amino acid alteration on protein expression, function, and stability. Many studies which involve the mutation of N-glycosylation sites on a glycoprotein also use simultaneous multi-site mutation to investigate whether the combined impact of losing two or more N-glycans differs from the effect observed following loss of a single N-glycan ( 52 , 60 , 61 ). This is a strategy that could reveal crucial information about the synergistic roles of N-glycans on the Notch1 ECD.…”
Section: Discussionmentioning
confidence: 99%